The Road to modern art 1800-1900 (Northbrook, Ill. Roland Films, 1986)
Features works of Delacroix, Courbe, Corot, Cezanne, Pisarro, Monet, Manet, Renoir, Degas, Seurat, Van Gogh, and Rousseau.
VHS format.
Director, Henry Lewes ; written and narrated by Edwin Mullins.
Keywords: Impressionism (Art).; Painting -- History -- Europe; Painting, Modern -- 19th century